Penerapan Metode Job Order Costing Dalam Penetapan Harga Pokok Produksi Pada Ukm J’rami Farm: Job Order Costing Method Application for Production Costs at J'Rami Farm SMEs - Salsabila, Difa; Dewi, Anggita Fitriana; Yudyanto, Rizqa Syahirah; Tartiani, Yuni Astuti Tri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study analyzes the application of the Job Order Costing method in determining the Cost of Goods Manufactured (COGS) at SME J'rami Farm in Bogor using a case study approach with data collection methods through interviews, observation, and document analysis. The results showed that the application of the Job Order Costing method provides a more accurate calculation compared to the method that has been used so far, thus enabling the company to set a more optimal profit margin and helping the company improve production cost efficiency. The application of this method also provides opportunities for SMEs to develop their business and be able to compete better in the market